Manajemen Mutu Terpadu Perguruan Tinggi - Shalahudin, Shalahudin (Al-Fikrah, 2011)
The problem facing education is the lack of quality output, management, human resources, and weak ability to compete in the Global World Arena. This is Evidences by the increasing number of educated unemployment and lack of student academic achievement. To that end, expert of management education (total quality management) quality (TQM) as Joseph M. Juran and his colleagues offer in order to implement TQM in a consistent and continuous. By involving all components of the organization to improve the quality of higher education. At the implementation level there are four pillars of TQM are: customer statisfaction, respect for all people, management by facts, and continuas improvements. In any quality improvement activity must implement four-step plan, control, and quality improvement. As the spear head TQME is a leader who has a high work ethic, consistent, and democratic.